2006
DOI: 10.1016/j.febslet.2006.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of rat liver mitochondria reveals a possible compensatory response to endotoxic shock

Abstract: Organ failure induced by endotoxic shock has recently been associated with affected mitochondrial function. In this study, effects of in vivo lipopolysaccharide-challenge on protein patterns of rat liver mitochondria in treated animals versus controls were studied by two-dimensional electrophoresis (differential image gel electrophoresis). Significant upregulation was found for ATP-synthase a chain and superoxide dismutase [Mn]. Our data suggest that endotoxic shock mediated changes in the mitochondrial proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…One clue is the observation of an up-regulation of the ␤ chain of the mitochondrial ATP synthase as up-regulation of ATP synthase by toxicants has been attributed to an adaptation of the cells to mitochondrial damage induced by ROS (52,53). For liver mitochondria of rats treated with lipopolysaccharide, up-regulation of the ATP synthase ␣ chain was shown to be accompanied by an up-regulation of mitochondrial manganese-dependent superoxide dismutase (SOD2), and the expression of both enzymes was correlated with ROS generation suggesting that it represented a coordinated response to compensate for low levels of ATP and to increase mitochondrial antioxidant capacity (53). In fact, for rat and mouse liver, the induction of mitochondrial oxidative stress by TCDD is well established (88 -91).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One clue is the observation of an up-regulation of the ␤ chain of the mitochondrial ATP synthase as up-regulation of ATP synthase by toxicants has been attributed to an adaptation of the cells to mitochondrial damage induced by ROS (52,53). For liver mitochondria of rats treated with lipopolysaccharide, up-regulation of the ATP synthase ␣ chain was shown to be accompanied by an up-regulation of mitochondrial manganese-dependent superoxide dismutase (SOD2), and the expression of both enzymes was correlated with ROS generation suggesting that it represented a coordinated response to compensate for low levels of ATP and to increase mitochondrial antioxidant capacity (53). In fact, for rat and mouse liver, the induction of mitochondrial oxidative stress by TCDD is well established (88 -91).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we observed significant alterations of two components of the respiratory chain, namely a down-regulation of ubiquinol-cytochrome c reductase core protein I (UQCRC1, number 40), a core subunit of mitochondrial respiratory complex III, and an up-regulation of the ␤ chain of the mitochondrial ATP synthase (number 41). Up-regulation of the latter is a characteristic cellular response to certain toxicants that has been attributed to an adaptation of cells to mitochondrial damage induced by ROS (52,53).…”
Section: Known and Putative New Members Of The Ahr And Are Genementioning
confidence: 99%
“…In a study on rat mitochondria of controls and LPS-challenged animals [188], two spots identified as cytochrome c oxidase were among potentially interesting candidates for differentially expressed spots. An experiment with reverselabeled samples showed that this was not a true difference: spots gave higher values in Cy3 labelling and scanning with Figure 9.…”
Section: Single Proteins and Their Behavior In Labeling With Cydyesmentioning
confidence: 99%
“…An experiment with reverselabeled samples showed that this was not a true difference: spots gave higher values in Cy3 labelling and scanning with Figure 9. Examples for protein spots with differential labeling with CyDyes: close-ups and Cy3/Cy5 ratios for (A) canine apolipoprotein A-I in dog serum (identification by immunoblot, own unpublished results); (B) cytochrome c oxidase in rat liver mitochondria preparations: spots were identified by MS [188] with accession numbers P11240 for spot 1019 (cytochrome c oxidase polypeptide subunit Va) and P12075 for spot 1004 (subunit Vb); (C) tropomyosin in transfected cat kidney cells (spots identified by MS [189] with accession numbers P07951 and P09493 for spot 355 and Q5VU66 and P67936 for spot 399).…”
Section: Single Proteins and Their Behavior In Labeling With Cydyesmentioning
confidence: 99%
“…Human short chain 3-hydroxyacyl-CoA dehydrogenase (SCHAD) deficiency is an inherited defect in mitochondrial fatty acid oxidation [31]. Significant upregulaton of catalase and 3-hydroxyacyl-CoA dehydrogenase might be due to compensatory reaction to endotoxic shock of brucella [22]. In other words, septic shock may induce ATP depletion that may cause an increase in peroxisomal β-oxidation in order to produce ATP, while abundant H2O2 may be produced during peroxisomal β-oxidation [12].…”
Section: Discussionmentioning
confidence: 99%